Frameless angiogram-based stereotactic radiosurgery for treatment of arteriovenous malformations. - Lu XQ; Mahadevan A; Mathiowitz G; Lin PJ; Thomas A; Kasper EM; Floyd SR; Holupka E; La Rosa S; Wang F; Stevenson MA; Lu, Xing-Qi; et al. (International Journal of Radiation Oncology, Biology, Physics, 2012)
Purpose: Stereotactic radiosurgery (SRS) is an effective alternative to microsurgical resection or embolization for definitive treatment of arteriovenous malformations (AVMs). Digital subtraction angiography (DSA) is the gold standard for pretreatment diagnosis and characterization of vascular anatomy, but requires rigid frame (skull) immobilization when used in combination with SRS. With the advent of advanced proton and image-guided photon delivery systems, SRS treatment is increasingly migrating to frameless platforms, which are incompatible with frame-based DSA. Without DSA as the primary image, target definition may be less than optimal, in some cases precluding the ability to treat with a frameless system. This article reports a novel solution. Methods and Materials: Fiducial markers are implanted into the patient's skull before angiography. Angiography is performed according to the standard clinical protocol, but, in contrast to the previous practice, without the rigid frame. Separate images of a specially designed localizer box are subsequently obtained. A target volume projected on DSA can be transferred to the localizer system in three dimensions, and in turn be transferred to multiple CT slices using the implanted fiducials. Combined with other imaging modalities, this "virtual frame" approach yields a highly precise treatment plan that can be delivered by frameless SRS technologies. Results: Phantom measurements for point and volume targets have been performed. The overall uncertainty of placing a point target to CT is 0.4 mm. For volume targets, deviation of the transformed contour from the target CT image is within 0.6 mm. The algorithm and software are robust. The method has been applied clinically, with reliable results. Conclusions: A novel and reproducible method for frameless SRS of AVMs has been developed that enables the use of DSA without the requirement for rigid immobilization. Multiple pairs of DSA can be used for better conformality. Further improvement, including using nonimplanted fiducials, is potentially feasible.